Relationship between phenotypes of cell-function differentiation and pathobiological behavior of gastric carcinomas - Xin, Yan (World journal of gastroenterology : WJG, 2001)
To reveal the correlation between the functional differentiation phenotypes of gastric carcinoma cells and the invasion and metastasis by a new way of cell-function classification. Surgically resected specimens of 361 gastric carcinomas(GC) were investigated with enzyme-, mucin-, and tumor-related marker immunohistochemistry. According to the direction of cell-function differentiation, stomach carcinomas were divided into five functionally differentiated types. (1) Absorptive function differentiation type (AFDT): there were 82 (22.7%) patients including 76 (92.7%) aged 45 years. Sixty-nine (84.1%) cases belonged to the intestinal type. Thirty-eight (46.3%) expressed CD44v6 and 9 (13.6%) of 66 male patients developed liver metastasis. The 5-year survival rate of patients in this group (58.5%) was higher than those with the other types (P<0.01). (2) Mucin secreting function differentiation type (MSFDT): 54 (15%) cases. Fifty-three (98.1%) tumors had penetrated the serosa, 12 (22.2%) expressed ER and 22 (40.7%) expressed CD44v6. The postoperative 5-year survival rate was 28.6%. (3) Absorptive and mucin-producing function differentiation type (AMPFDT): there were 180 (49.9%) cases, including 31 (17.2%) aged younger than 45 years. The tumor was more common in women (62, 34.4%,) and expressed more frequently estrogen receptors (ER) (129, 81.7%) than other types (P<0.01). Ovary metastasis was found in 12 (19.4%) out of 62 female subjects. The patients with this type GC had the lowest 5-year survival rate (24.7%) among all types. (4) Specific function differentiation type (SFDT): 13 (3.6%) cases. Nine (69.2%) tumors of this type derived from APUD system, the other 4 (30.7%) were of different histological differentiation. Sixty per cent of the patients survived at least five years. (5) Non-function differentiation type (NFDT): 32 (8.9%) cases. Nineteen (59.4%) cases had lymph node metastases but no one with liver or ovary metastasis. The 5-year survival rate was 28.1%. This new cell-function classification of GC is helpful in indicating the characteristics of invasion and metastasis of GC with different cell-function differentiation phenotypes. Further study is needed to disclose the correlation between the cell-functional differentiation phenotypes and the relevant genotypes and the biological behavior of gastric carcinoma.